Law Journals: From Discourse to Pedagogy - Ilija Vickovich (Legal Education Review)
Law students face a number of challenges when entering the employment market. Apart from stiff competition from their peers, there is often disconnect between the theory they are taught in law courses and the realities of legal practice they are faced with when stepping into the “real world”. At some universities, this discrepancy is partly addressed by legal skills programmes, but there is still a significant leap from ‘student’ to ‘early career lawyer’. In this regard, clinical experience can be an invaluable asset to graduates - a law teaching clinic has the potential to advance student involvement and practical engagement to a new level. This article focuses on the benefits of experiential learning in a pro bono teaching clinic and considers the advantages of consciously incorporating service learning into such a clinic, with reference to a case study of a successful commercial law teaching clinic established within a university law faculty. It also examines the challenges and considerations inherent in establishing a teaching pro bono clinic within a law school, and suggests solutions for implementing an effective model, thereby enhancing student employability